The Influence Of Customer Relationship Management (Crm) And Customer Satisfaction On Customer Loyalitas At My Lova Fashion Store In Bengkulu City - Sellina Dwi Anjjely; Eska Prima Monique D; Sri Handayani (Universitas Dehasen Bengkulu, 2026)
Business competition in the fashion industry, particularly in Bengkulu City, is becoming increasingly intense, so stores need to implement appropriate strategies to retain customers. My Lova Bengkulu store attempts to build good relationships with customers through the implementation of Customer Relationship Management (CRM) and improvements in Customer Satisfaction. This study aims to determine the extent to which the implementation of Customer Relationship Management (CRM) and customer satisfaction affect customer loyalty, both partially and simultaneously. This study uses a quantitative approach with a survey method. Based on the research characteristics, the obtained sample consisted of 100 respondents who are customers of My Lova store in Bengkulu City. Data were collected through questionnaires using a non-probability sampling method. The analysis used multiple linear regression to determine the influence between the independent and dependent variables in this study. The results of the multiple linear regression test produced the equation Y = -4.035 – 0.568X1 + 1.631X2 + 2.852. The t-test shows that the Customer Relationship Management (CRM) variable has a significant effect on customer loyalty with a significance value of 0.000 < 0.05. This indicates that the implementation of Customer Relationship Management (CRM) at My Lova Store has been optimally carried out in building strong relationships with customers. The Customer Satisfaction variable also has a significant effect on customer loyalty with a significance value of 0.000 < 0.05, meaning that the higher the customers’ satisfaction with the store’s products and services, the higher their loyalty. Simultaneously, both variables have a significant effect on customer loyalty with a coefficient of determination (R²) of 0.791, which means the implementation of Customer Relationship Management (CRM) and customer satisfaction can explain 79.1% of customer loyalty, while the remaining 20.9% is influenced by other variables not examined in this study.